[PP.07.29] BLOOD PRESSURE VARIABILITY IS INCREASING FROM THE FIRST TO THE SECOND DAY OF THE INTERDIALYTIC INTERVAL IN HEMODIALYSIS PATIENTS. (September 2017) - Karpetas, A.; Loutradis, C.; Lazaridis, A.; Bikos, A.; Tzanis, G.; Koutroumpas, G.; Mavromatidis, K.; Liakopoulos, V.; Zebekakis, P.; Ruilope, L.M.; Parati, G.; Sarafidis, P.S.
Abstract : Objective: Patients with end-stage-renal-disease under hemodialysis have increased cardiovascular risk and experience severe BP fluctuations during the dialysis session and the subsequent interdialytic period. BP variability (BPV) may be an additional risk factor for cardiovascular events and preliminary data suggest increased BPV with advancing stages of CKD. This is the first study to examine BPV during the whole intra- and interdialytic period in hemodialysis patients with ambulatory blood pressure monitoring (ABPM). Design and method: A total of 160 patients receiving maintenance hemodialysis had 48-hour ABPM with the Mobil-o-Graph device during a regular dialysis session and the subsequent interdialytic interval. Brachial and aortic BPV were calculated with validated formulas and were compared between Day 1 and Day 2 of the interdialytic period (44-hours), Day 1 and Day 2 of the total 48-hour interval (including the dialysis session), and between the two respective daytime periods and nighttime periods. Results: All brachial systolic BPV indices [standard deviation (SD): 14.75 ± 4.38 vs 15.91 ± 4.41, p = 0.001; weighted SD (wSD): 13.80 ± 4.00 vs 14.89 ± 3.90, p < 0.001; coefficient of variation (CV): 11.34 ± 2.91 vs 11.93 ± 2.94, p = 0.011; average real variability (ARV): 11.38 ± 3.44 vs 12.32 ± 3.65, p < 0.001)] were increasing from Day 1 to Day 2 of the 44-h interdialytic period. Similarly, all indexes of diastolic BP variability were significantly increased in Day 2, with the exception of CV. Aortic systolic and diastolic BPV indices displayed a similar pattern. Further, all studied brachial systolic and diastolic BPV indexes were also lower during daytime 1 than daytime 2 (systolic ARV 11.56 ± 3.98 vs 12.44 ± 4.03, p = 0.002); systolic ARV was lower in nighttime 1 compared to nighttime 2 (11.20 ± 5.09 vs 12.18 ± 4.66, p = 0.045). In multivariate analysis pre-dialysis SBP, age, diabetes, heart failure and use of statins were independently associated with increased SBP ARV. Conclusions: BPV is increased in Day 2 compared to Day 1 of the interdialytic period in hemodialysis patients; this could be another mechanism involved in the complex cardiovascular pathophysiology and increased cardiovascular mortality of these individuals.